If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -4) + -6x = 10 Reorder the terms: 7(-4 + x) + -6x = 10 (-4 * 7 + x * 7) + -6x = 10 (-28 + 7x) + -6x = 10 Combine like terms: 7x + -6x = 1x -28 + 1x = 10 Solving -28 + 1x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 1x = 10 + 28 Combine like terms: -28 + 28 = 0 0 + 1x = 10 + 28 1x = 10 + 28 Combine like terms: 10 + 28 = 38 1x = 38 Divide each side by '1'. x = 38 Simplifying x = 38
| 3.2m+12=3m-31 | | 3y-7-2y=7 | | 15a-15=8a+2+60 | | 3x+25=75 | | 7w=112 | | 21=fraction | | 7x-14=6x-14 | | X*X+1*X+2=3360 | | 71+s=229 | | 6q=-3 | | x-45=-78 | | 18+4y=-2(6+2y) | | m-17=58 | | 3(g+1)=12 | | 5=z+4 | | 2.25y+16.8=25.8 | | -4=3(3x-5)-2(5x-1)+9 | | x^2+3x-4.25=0 | | 0.4m-2.8=3.24 | | -9=3(g+-2)+-6 | | X(X+1)(X+2)=1360 | | 0.25(8j-4)=j+8-2j | | x+-45=77 | | 2x-7=x+15 | | -9=3(g+-2)+ -6 | | 4(x-2)+3(x+8)=-12 | | -9 = 3 ( g+ -2)+ -6 | | 0.2(7+2t)=0.4+1.4t | | 6.6x^2-169x-2855=0 | | x-(-0.2)=0.666666667 | | -4(v-2)=-4(v-8)-8 | | 25x^2+0=9 |